Miniaturized, focusing fan-out elements: design, fabrication and characterization - Schilling, Andreas; Nussbaum, Philippe; Ossmann, Ch.; Traut, S.; Rossi, Markus; Schift, H.; Herzig, Hans-Peter (My University, 1999)
We present miniaturized, focusing fan-out elements. The new micro-optical elements were fabricated using different technologies: double-sided injection moulding in polycarbonate, double-sided photolithography with subsequent transfer in quartz and direct laser writing in photoresist. The fan-out elements were characterized by measuring their efficiency and uniformity, the surface profiles of the microlenses were measured with a Twyman-Green interferometer. The overall performance of the combined, hybrid elements is demonstrated with intensity distributions recorded in the focal planes.
Keywords: focusing fan-out; injection moulding; reactive ion etching; direct laser writing; optical interconnects